A NEW CYCLE TO RE-EDIFY THE WELFARE STATE IN ARGENTINA. LABOR AND SOCIAL POLICIES BETWEEN 2003-2015 - Grassi, Estela (2016)
This article describes the main features of the State reconfiguration that took place during the first decade of 21th Century in Argentina which allow us to define it as an updated  (or modernized) return of the Welfare State. This characterization is based upon the analysis of two courses of action taken by the social policy of the current political cycle: 1) The recovery/restitution of the character of “normal” for full-time employment, with indefinite time hiring and social security protection which led to the installation of social security as the core of social policy in this period. This traditional protection coexists with 2) the development of social security system reforms that allowed to enhance protections to informal workers and long-term unemployed. Notwithstanding how contradictory these measures can be considered, the official state discourses and ideological foundations of both courses of action reinforce the symbolic horizon of expectations to include the entire working population to those conditions of “normal work”.